2019
DOI: 10.1371/journal.pone.0214521
|View full text |Cite
|
Sign up to set email alerts
|

An unconventional RNA-based thermosensor within the 5’ UTR of Staphylococcus aureus cidA

Abstract: Staphylococcus aureus is a Gram-positive bacterial pathogen of global concern and a leading cause of bacterial infections worldwide. Asymptomatic carriage of S . aureus on the skin and in the anterior nares is common and recognized as a predisposing factor to invasive infection. Transition of S . aureus from the carriage state to that of invasive infection is often accompanied by a temperature upshift from ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Other than the closed conformation identified by Hussein et al. ( 65 ), we could also predict by mfold a putative alternative conformation in the longer cidA 5′UTR that would make the RBS available to the ribosome at low temperatures ( Supplementary Figure S8 ). This open conformation would involve a long hairpin comprising nucleotides 5–66 of the cidA 5′UTR that would sequester the anti-RBS motif ( Supplementary Figure S8 ), resembling the mechanism found for CspB and CspC.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Other than the closed conformation identified by Hussein et al. ( 65 ), we could also predict by mfold a putative alternative conformation in the longer cidA 5′UTR that would make the RBS available to the ribosome at low temperatures ( Supplementary Figure S8 ). This open conformation would involve a long hairpin comprising nucleotides 5–66 of the cidA 5′UTR that would sequester the anti-RBS motif ( Supplementary Figure S8 ), resembling the mechanism found for CspB and CspC.…”
Section: Discussionmentioning
confidence: 63%
“…These type of RNA structural rearrangements, which repress translation at higher temperatures while activating it at lower temperatures, are also present in the 5′UTR of the bacteriophage cIII gene ( 64 ). Recently, regulatory 5′UTRs that activate the expression of the holin-like protein CidA at low temperatures have been described for S. aureus ( 65 ). Hussein et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, using Northern blot analysis, Seidl et al (19) demonstrated that inactivation of the ccpA gene in S. aureus leads to a significant decrease in the accumulation of cidABC transcripts during the exponential phase of growth. Interestingly, in addition to the transcriptional control of cidABC expression, recent work by Hussein et al (20) revealed the presence of a functional thermosensor within the 5= untranslated region (UTR) of the cidA gene, which posttranscriptionally facilitates increased cidABC expression at lower temperatures.…”
mentioning
confidence: 99%
“…At 37°C, the energy provided by the increased temperature is sufficient to cause a structural switch that enables translation of the TF. Additional thermometers are found in many pathogens such as Salmonella Typhi and S. aureus ( Hussein et al, 2019 ; Brewer et al, 2021 ; Catalan-Moreno et al, 2021 ), and have been extensively reviewed ( Loh et al, 2018 ).…”
Section: Classification Of Base-pairing Acting Srnas According To Their Origins and Mechanisms Of Actionmentioning
confidence: 99%